Policy Learning as a Strategy to Strengthen Collaborative Governance in Public Services: Theoretical and Practical Perspectives - Martikalini, Citra; Alfitri; Sriati; Thamrin, M. Husni (Department of Public Administration, 2025)
Collaborative governance in public services is an increasingly important approach amidst the complexity of problems faced by the government. Various actors with different interests must interact and work together to create effective and efficient services. However, the challenges faced in this collaboration often involve tensions between bureaucratic structures and horizontal cooperation between stakeholders. Policy learning is an important element in responding to these dynamics and strengthening collaborative processes in public governance. This study aims to explore the role of policy learning in strengthening collaborative governance in public services. This study uses a qualitative approach by collecting data from various sources, such as previous studies, research results, and relevant policy documents, to analyze the dynamics of collaboration and learning between actors. The results show that policy learning is key in creating a shared understanding between the actors involved. In addition, effective collaboration can be achieved with an inclusive and sustainable learning mechanism, as well as strong institutional support. This study suggests the importance of integrating policy learning into collaborative governance strategies to ensure the sustainability and success of better public services.